Interdialytic Weight Gains Dan Kram Otot Selama Penarikan Cairan Pasien Hemodialisis - Muhammad Putra Ramadhan; Ahmad Masfi; Ronal Surya Aditya; Eri Yanuar Achmad Budi Sunaryo; Qory Tifani Rahmatika; Yhenti Widjayanti; Nurul Evi; Nurma Afiani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  To identify the relationship of weight gains between two dialysis periods levels with muscle cramps in patients during hemodialysis.Methods:  This was a descriptive analytical study, which 90 patients undergoing HD was recruited using consecutive sampling.Results: There is a relationship between weight gains between two dialysis periods levels and muscle cramps at the 4th hour of hemodialysis (pvalue  < α; α = 0.05). Based on this study, weight gains between two dialysis times was associated with muscle cramps at the 4th hour of hemodialysis.Conclusion:  Based on this study, weight gain between two dialysis times was associated with muscle cramps at the 4th hour of hemodialysis. Hospitals need to establish regulations in the form of clinical guidance on monitoring patient complaints every hour during hemodialysis.